Effects of Electro-Acupuncture and Acupotomy Dissolution on mRNA Expression of Center Pro-Opiomelanocortin Detected by In Situ Hybridization in Rats with Non-Specific Low Back Pain: - Badiee Aval, Shapour; Khorsand, Ali; Mojtabavi, Seyed Javad; Rezaei Deloei, Shima; Qin, Guo Chang (Galen Medical Journal, 2016)
Background: Pro-opiomelanocortin (POMC) mainly exists in the pituitary gland, hypothalamus, and peripheral tissues and can relieve pain through its degradation product Î²-endorphin. Its mRNA expression quantity represents the level of gene expression of endorphin system. We aimed to determine the effects of electro-acupuncture and acupotomy dissolution on the mRNA expression of center POMC in rats with non-specific low back pain.Materials and Methods: This study was performed on 42 Sprague-Dawley rats in four groups of normal, model, electro-acupuncture, and acupotomy. The normal group did not receive any intervention, while non-specific low back pain was established in other groups. Then, the model group did not receive any treatment, electro-acupuncture and acupotomy groups were treated with electro-acupuncture therapy and acupotomy, respectively. Microscopic images of the slices, prepared from spinal dorsal horn and hypothalamus, were analyzed to evaluate the mRNA expression of center POMC. Results: Under light microscopy examination, the positive POMC mRNA cells of electro-acupuncture and acupotomy groups increased more than the model group, while its expression in the hypothalamus and spinal dorsal horn was less than the model group, but the difference was not significant (P<0.01). Conclusion: Electro-acupuncture and acupotomy could reduce POMC mRNA expression in spinal cord and increase it in the hypothalamus of rats with non-specific low back pain.[GMJ.2016;5(4):194-99]